Design and evaluation of a maize mini-combine harvester for smallholder farmers : technical report - López Gómez, Jesús Antonio; Loon, Jelle J. van (International Maize and Wheat Improvement Center, 2023)
Harvesting in maize production is one of the activities that requires the greatest investment of time and physical effort for those who perform it manually. The existence of specialized machinery for this particular activity is focused on the medium and high production sector, who usually use tractors or high-powered self-propelled machines. However, small maize producers in Mexico face the problem that sometimes do not have the capacity for timely harvesting and cannot rely on service providers who tend to prioritize large extensions and with machine far too large to enter in small plots. In response, a maize mini-combine harvester prototype for a Dongfeng® two-wheel tractor with 15 hp of power was developed. This report describes the development process and tests conducted both in the mechanical workshop and in a field with maize crop. Performance parameters such as work capacity, fuel consumption, mechanical damage to harvested grain and losses due to corn grain dispersion in the field were determined. The favorable results show the developed mini-combine harvester as an option to mechanize the harvesting activity, using power sources according to the working surfaces, which is also reflected in the low fuel consumption compared to medium-power agricultural tractors.